Effect of chronotype on emotional processing and risk taking. (20th April 2016) - Berdynaj, Donjeta; Boudissa, Sarah N.; Grieg, Magnus S.; Hope, Charlotte; Mahamed, Sacdiya H.; Norbury, Ray
ABSTRACT: There is increasing evidence to suggest that late chronotypes are at increased risk for depression. The putative psychological mechanisms underpinning this risk, however, have not been fully explored. The aim of the present study was to examine whether, similar to acutely depressed patients and other "at risk" groups, late chronotype individuals display biases in tasks assaying emotional face recognition, emotional categorisation, recognition and recall and attention. Late chronotype was associated with increased recognition of sad facial expressions, greater recall and reduced latency to correctly recognise previously presented negative personality trait words and reduced allocation of attentional resources to happy faces. The current results indicate that certain negative biases in emotional processing are present in late chronotypes and may, in part, mediate the vulnerability of these individuals to depression. Prospective studies are needed to establish whether the cognitive vulnerabilities reported here predict subsequent depression.